Genesis of legal regulation of overcoming resistance to investigation - Tarkan, Oleksandr (Archives of Criminology and Forensic Sciences, 2025)
Legal regulation of obstruction of investigation gradually transformed from fragmentary prohibitions in the most ancient sources to a holistic comprehensive approach in the modern criminal legislation of Ukraine. Key factors of this evolution were strengthening of the role of justice, the complication of forms of illegal influence and the need for effective institutional and procedural protection against it. This article purpose was to determine specifics of doctrine formation of criminalization of acts that have signs of obstruction of investigation and trial. It was established that in the most ancient times, in particular in documents from the era of Ramses IX in Ancient Egypt, attempts to conceal crimes or influence witnesses were already recorded, however, the legal regulation of such actions was not yet of a systemic nature. In the Middle Ages, the first formalized norms of legal liability for actions that impede trial were laid down. Thus, «Руська Правда» contained provisions on punishment for encroachments on representatives of the judiciary and for knowingly false denunciations. Lithuanian statutes detailed liability of witnesses, and also determined the punishment for falsification and unlawful interference in the judicial process. In the period of the 18th - early 19th centuries, the systematization of liability for obstruction of justice can be traced. In the late 19th - early 20th centuries, the Criminal Code of 1903 for the first time systematically covers the entire range of actions that obstruct justice. In the Soviet period, legal regulation continued its development with the division of crimes into actions of officials (for example, making a knowingly unjust decision) and other participants in the judicial process (perjury, pressure on investigators, falsification). Criminal codes contained provisions on liability for actions that obstructed the investigation, as well as on interference in the work of the court. Considerable attention was paid to ideological control over the justice system. The modern stage of development begins with the adoption of the Criminal Code of Ukraine in 2001.